Formation of porous structure in paramylon esters via supercritical CO₂ - Seisuke Ata; Takumi Ono; Motonari Shibakami (eXPRESS Polymer Letters, 2025)
This study demonstrated, for the first time, the successful formation of porous paramylon esters, which were made from euglenoid polysaccharide known as paramylon and short-chain fatty acids, through supercritical CO2 processing. By maintaining a constant ester functional group attached to the paramylon and varying its proportion, distinct porous structures were selectively produced. Solubility parameter estimations indicated that changes in esterification had no significant effect on the solubility of the paramylon esters used in the experiment. Thus, these structural differences are likely attributed to variations in the viscoelastic properties of paramylon esters under supercritical CO2 conditions. Furthermore, thermal conductivity measurements revealed reductions of up to 20%. Intriguingly, substantial decreases in thermal conductivity were observed even at low foaming ratios, achieved through precise control of the porous structure.